Tanggung Jawab Hukum atas Terjadinya Wanprestasi yang Dilakukan oleh Tenaga Medis dalam Perjanjian Terapeutik - Ghalib Farisa (Jurnal Hukum Lex Generalis, 2025)
A therapeutic agreement serves as the legal basis binding the relationship between patients and medical personnel in the implementation of medical procedures. This agreement contains elements of mutual consent that set forth the rights and obligations of both parties, fundamentally aiming to provide legal protection for both patients and medical professionals. However, in practice, breaches of therapeutic agreements by medical personnel often occur, whether due to negligence, performing actions without informed consent, or violations of established medical service standards.This study aims to analyze the legal framework governing therapeutic agreements in Indonesia, the forms of legal liability of medical personnel for such breaches, and the legal remedies available to patients seeking compensation. The research employs a normative juridical approach, utilizing statutory and doctrinal methods, and is analyzed based on written legal norms, legal literature, and regulations related to medical practice.The findings indicate that therapeutic agreements are implicitly regulated in the Medical Practice Law, the Indonesian Civil Code, and regulations concerning consent to medical procedures (informed consent). If a medical professional is proven to have committed a breach, they may be held legally accountable in five forms: civil liability in the form of compensation, criminal liability if a criminal offense is involved, ethical liability through the Medical Ethics Honorary Council, disciplinary liability through the Indonesian Medical Discipline Honorary Council, and administrative sanctions imposed by the relevant authorities. Legal remedies for compensation may be pursued through civil lawsuits in court on the basis of breach of contract, as stipulated in Article 1243 of the Indonesian Civil Code. The enforcement of such legal responsibilities is expected to provide protection and legal certainty for patients, as well as to enhance the professionalism of medical personnel in practicing medicine in accordance with applicable ethical standards and procedures. Therefore, it is hoped that therapeutic agreements can operate in accordance with the principles of mutual trust, transparency, and shared responsibility.